Lipodistrofia entre pacientes infectados pelo HIV em tratamento antirretroviral: uma revisão sistemática da literatura - Lorena Gomes Cunha Lana (2014)
Lipodystrophy is a major adverse reaction to prolonged use of antiretroviral therapy (ART). Aiming to describe the occurrence of lipodystrophy among HIV-infected patients exposed to ART, a systematic review of the literature of observational studies was carried out. A sensitive search was performed on five databases (MEDLINE, CINAHL, LILACS, EMBASE e International Pharmaceutical Abstracts) until June, 2014. Observational studies investigating the occurrence of lipodystrophy as primary or secondary outcome and comparing HIV-infected patients on different ART during at least six months were considered eligible. The main measure of occurrence was the frequency (incidence and prevalence) of lipodystrophy. In addition, lipoatrophy and lipohypertrophy were also considered for analysis. Altogether, 20 studies were included in the systematic review - 12 cross-sectional and eight prospective studies. Sixteen (80%) of the studies provided detailed information on the definition of lipodystrophy, describing the anatomical sites and four (20%) reported the outcome in vague and unspecific terms. In general, all the studies evaluating the outcome lipodystrophy investigated morphological alterations in the abdomen, face and members, including or not other anatomical sites. Some studies additionally took into account the severity of the outcome. The diagnostic method varied among the studies (n=4; 20%), being the concomitant evaluation of the physician and the patient the most used (n=9; 45%). Considering the outcomes in general and according to the reported nomenclature in the primary studies, the results demonstrated that the prevalence of lipodystrophy ranged between 11.7% a 67.8% and the most prevalent phenotype was mixed lipodystrophy (39.9%). The incidence of lipodystrophy ranged between 8.1% and 52.0%. The punctual prevalence of lipodystrophy was less heterogeneous than the incidence. The prevalence reported in the included studies was concentrated around 58.3% and 60.1%, and this seems to be related to some similarities in the employed outcome definitions, since the diagnostic methods were diverse. The occurrence of the outcome was mainly investigated in relation to comparative exposures between exposed and non-exposed to protease inhibitors (PI) (n=4; 26.7%) and between zidovudine and stavudine (n=4; 26.7%). The associations between lipodystrophy and ART most investigated correspond to the antiretroviral classes and antiretroviral drugs considered main risk factors for lipodystrophy in the current literature. This observation would be anticipated since PI and the thymidine nucleoside analogue reverse transcriptase inhibitors had been prescribed as first- line ART regimens in several countries. Currently, the available knowledge concerning the risk factors associated with the occurrence of lipodystrophy is originated from studies evaluating different outcomes. In conclusion, the assessment of the association between lipodystrophy and specific antiretroviral drugs should be carefully evaluated as limitations of the available studies make this analysis impossible, essentially because they are not evaluating uniformly the same clinical condition. Moreover, these limitations precluded the comparative evaluation of the reported risk determinants. In view of this, it is imperative to carry out studies focusing on the precise lipodystrophy definition, contributing to the standardization of a diagnostic method and to the determination of risk factors.